2020
DOI: 10.1371/journal.pone.0237429
|View full text |Cite
|
Sign up to set email alerts
|

Permissive parenting of the dog associates with dog overweight in a survey among 2,303 Dutch dog owners

Abstract: Overweight/obese dogs are at increased risk of health issues and it is up to the dog owner to uphold successful weight management. In children, overweight relates to their parent's permissive style of parenting. We predicted that permissive dog-directed parenting likewise associates with a dog being overweight (including obesity). If styles in parenting dogs indeed associate with a dog's overweight, these may provide action points for effective weight management. For 2,303 Dutch dog owners, answers on their do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
5
0
3
Order By: Relevance
“…Companion dogs are often regarded as family members and often share a lifestyle with their owners [ 1 ]. It has been shown that the owner’s education, family income, parenting style and attitude towards healthy food and physical activity may influence the BCS of a dog [ 2 , 46 ]. Awareness of obesity is another important factor to address, as dog owners who do not consider obesity a disease are more likely to have an overweight dog [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Companion dogs are often regarded as family members and often share a lifestyle with their owners [ 1 ]. It has been shown that the owner’s education, family income, parenting style and attitude towards healthy food and physical activity may influence the BCS of a dog [ 2 , 46 ]. Awareness of obesity is another important factor to address, as dog owners who do not consider obesity a disease are more likely to have an overweight dog [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Las recomendaciones alimenticias en productos alimenticos comerciales presentan su cálculo en un animal promedio, modelo de predicción que no considera la actividad física del animal, si se encuentra esterilizado (Oberbauer et al, 2019), si es una hembra o un macho (Bjørnvad et al, 2019), si convive con otros animales, el espacio físico en el cual se mantiene (Torda-Orsolya et al, 2020), si reciben aperitivos o meriendas (Pearl et al, 2020) y las características de los dueños (van Herwijnen et al, 2020).…”
Section: Discussionunclassified
“…De igual manera, la costumbre del ser humano a ofrecer una cantidad adicional de alimento, por encima de lo recomendado, estimula al animal a aumentar el consumo voluntario (Kersbergen et al, 2019), lo que podría promover una situación de suministro excesivo de nutrimentos, que provoca en los animales de compañía el sobrepeso, diabetes, problemas musculares (van Herwijnen et al, 2020), problemas cardiorespiratorios y desordenes urinarios (Roberts, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Recent research suggests that aspects of human psychology may drive how people care for animals [ 1 , 2 ]. Specifically, attachment theory has been used to examine caregiving and attentiveness towards pets [ 1 ].…”
Section: Introductionmentioning
confidence: 99%